Editor's Choice – Minimizing Radiation Exposure During Endovascular Procedures: Basic Knowledge, Literature Review, and Reporting Standards. Issue 1 (July 2015) - Hertault, A.; Maurel, B.; Midulla, M.; Bordier, C.; Desponds, L.; Saeed Kilani, M.; Sobocinski, J.; Haulon, S.
Abstract : Context: Endovascular procedures, requiring X-ray guidance, are commonly performed in vascular surgery. X-ray exposure is associated with biological risks for both patients and physicians. Medical X-ray use must follow "as low as reasonably achievable" (ALARA) principles, which aim at using the lowest radiation exposure to achieve a procedure safely. This is underlined by European and international recommendations that also suggest that adequate theoretical and practical training is mandatory during the initial education of physicians. However, the content of this education and professional practices vary widely from one country to another. Objective: This review aims to summarize the basic knowledge required for vascular surgeons on X-ray physics and image production. Methods: A panel of endovascular therapists (vascular surgeons and radiologists) and physicists dedicated to X-rays was gathered. International recommendations were summarized. A literature review was performed via MEDLINE to identify studies reporting dosages of common endovascular procedures. Results: The different mechanisms inducing biological risks, and the associated potential effects on health, are described. Details on dose metrics are provided and a common nomenclature to measure, estimate, and report dose is proposed in order to perform accurate comparisons between publications and practices. Key points of the European and international legislation regarding medical X-ray use are summarized, and radiation protection basics for patients and staff, are detailed. Finally, a literature review is proposed for physicians to evaluate their practice. Conclusions: Today's trainees will be highly exposed to radiation throughout their practice. It is thus compulsory that they undergo dedicated radiation education during their initial training, and regular refresher sessions later. In daily practice, focus on dose reduction and monitoring of patient and staff exposure are mandatory.